Big data – BigData 2019 : 8th International Congress, held as part of the Services Conference Federation, SCF 2019, San Diego, CA, USA, June 25-30, 2019, Proceedings /: 8th International Congress, held as part of the Services Conference Federation, SCF 2019, San Diego, CA, USA, June 25-30, 2019, Proceedings. (2019) - Unknown
No abstract available